Necrotizing Soft-tissue Infections: An Orthopaedic Emergency. Issue 5 (1st March 2019) - Lee, Adam; May, Addison; Obremskey, William T.
Abstract : Necrotizing soft-tissue infections are caused by a variety of bacterial pathogens that may affect patients at any age or health status. This orthopaedic emergency initially presents with nonspecific signs such as erythema and edema. As the disease progresses, classic signs such as bullae, cutaneous anesthesia, ecchymosis, tense edema, and gas can be seen. A high level of suspicion is needed to properly identify and treat in a timely manner. Pain out of proportion to presentation and rapid progression even with appropriate antibiotic treatment should heighten suspicion of a necrotizing soft-tissue infection. The mainstay of management is extensive débridement and decompression of all necrotic tissue and broad-spectrum antibiotics. Débridements are repeated to ensure that disease progression has been halted. Early surgical débridements should take precedent over transfer because of the high rate of limb loss and mortality as a result of surgical delay.